DINAMIKA RELIGIOUS COPING DALAM MENGHADAPI KONFLIK PERAN GANDA: STUDI PADA SANTRI MAHASISWA PONDOK PESANTREN AL-MUSHLIH KARAWANG - Kusuma, Danuwangsa; Permana, Hinggil; Khulasoh, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the dynamics of religious coping in dealing with multiple role conflict among student-santri at Pondok Pesantren Al-Mushlih Karawang. The study employed a qualitative approach with a phenomenological design to explore the lived experiences and subjective meanings constructed by participants. Participants were selected through purposive sampling, consisting of santri who were actively pursuing higher education while residing in the pesantren. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that student-santri experience multiple role conflict due to the simultaneous demands of academic responsibilities and pesantren obligations, resulting in time-management difficulties, emotional pressure, and psychological fatigue. Religious coping emerged as the primary strategy used to address these challenges through practices such as dhikr, prayer, Qur’anic recitation, voluntary prayers, spiritual meaning-making, religious social support, and tawakal. These practices not only helped participants reduce stress and achieve psychological calmness but also enabled them to reinterpret role conflict as a test, learning process, and means of personal and spiritual growth. The study concludes that religious coping functions not only as a mechanism for psychological adaptation but also as a process of meaning-making that transforms the way student-santri understand and respond to multiple role conflict.